The Ecological Aspects of Culex pipiens (Diptera: Culicidae) in Central Iran. - Hossein Dehghan; Seyed Hassan Moosa-Kazemi; Javid Sadraei; Hassan Soleimani (Tehran University of Medical Sciences, 2014)
Background: The aim was to survey the specific factors, which cause to decrease blood feeding of mosquitoes important to succeed vector control. Methods: Larval collection was carried out from fixed and variable breeding places of Yazd County, central Iran in 2009. Autogeny-Anautogeny, Stenogamy-Eurygamy, and blood preference of Culex pipiens were studied using standard mosquito cages blood meal source for Cx. pipiens females considered as the chickens and human and fed females were kept in insectary condition (16:8 L: D, 27±3 °C and 70±10% RH). The data were analyzed using SPSS Ver. 11.5 soft ware. Results: Totally, 96 females' mosquitoes were tested for Stenogamy versus Eurygamy and 122 for blood preference assay. In the small cages (20× 20× 20cm) and large cage (60× 40× 60cm), the ability of mating and insemination rates were 60.0 and 67.0%, respectively. In spite of Cx. pipiens fed from sucrose 5%, none of them laying eggs in 60× 40× 60 cages during the study. This finding indicated the Anautogeny behavior of this species. This species was found of low tendency to human blood and almost 4 fold fed on chicken. Conclusion: The occurrence of Steno-Eurygamy, Anautogeny, and Ornithophilic behaviors of Cx. Pipiens was noted. More studies need to  be  carried out about the bionomics of this species to  gain more data about the ecophysiological and behavioral characteristics in other parts of Iran.